Effect of Omega-3 on Induced Cutaneous Wounds Healing in Rabbits (Medico Legal Update, 2020)
The present study was designed to evaluate the effects of omega3 on full-thickness cutaneous wounds healingin rabbits. All animals were created wound (1.5 cm2) full-thickness in dorsal back region in (16) male adultrabbits, clinically healthy weighing from (1.3- 1.8 kg). Under the effect of intramuscular administrationof a mixture of xylazine hydrochloride 5mg/kg with ketamine hydrochloride 35mg/kg of and 1 mg/kg ofDiazepam. The treatment group was given 300 mg of omega3 orally daily with single dose (group A), whilein group (B), the rabbits were left without treatment, as a control group. For clinical and histopathologicalevaluation, each group was divided into four subgroups (two wounds/subgroup) on 3, 7, 14 and 21th dayspost-wound creation and treatment. The result revealed, Clinically, the rate of wound healing was same inall groups, no differences when section taken from the edge of the wounds. The results histopathologically,shown the treated groups have greater cellularity with improved vasculature with the superiority of omega3 -treated groups than those in untreated groups. Conclusion; the histopathologically and clinically resultsconfirmed that given effects of omega3 to the treated groups leads to enhance and develop of cutaneouswound healing.